Sports Economics as an Academic Field: Sports Economics Theses and Common Themes in Turkey - Muazzez ŞAŞMAZ ATAÇOCUĞU (ümit doğan üstün, 2023)
The aim of this study is to examine common themes and the sub-study fields and research trends that stand out under these themes in the theses in the field of Sports Economics registered in the Higher Education Council (HEC) Thesis Center. For this purpose, the key word "Sports Economics" was entered on the main page of HEC Thesis Center and "All" was selected in the filters of the field, permission status, thesis type. In the study "Document Review" which is a research technique specific to "Qualitative Research Method" was applied. As a result of the search 50 records were found. Thesis are listed according to their years and examined under the titles of which program they are done (Master or Doctorate), institutes and departments, themes, methods and techniques. It has been that sports economics theses are mostly written at the Master's level and the majority of them written in the Institute of Social Sciences. According to departments in which theses are written sports economics is intensively studied in the field of economics such as Economics, Business Administration, Finance, Banking and Finance under the umbrella of economics and administrative sciences. As a result of the examination 5 main themes emerged. 1.Stock Exchange, 2.Sports Economics, 3.Sports Marketing, 4.Sport-Media and Economics, 5.Football Economics. Sub-study areas were determined under each main themes. It has been revealed that the general studies of sports economics are concentrated in the context of the economic effects of sports, especially in the field of football economics and the sports marketing. Although a certain trend graph does not emerge methodologically under the common themes that emerged in the theses examined, it can be said that both Amerikan and European sports economy methodology approaches are used when the methods and techniques used are examined. It is also seen that thesis studies started to increase after 2014. When a search is done with the key word "Sports" registered 18446 thesis appeared and 2000 of them are displayed. From this point of view, inadequacy of the theses in the field of sports economics in terms of number and the narrowness of the field of study are striking.